Physicochemical and sensory characteristics of whole, skimmed and lactose-free goat and bovine milks - Álvarez-Figueroa, María Laura (2022)
Introduction. The characterization and diversification of goat dairy products is very important to strengthen this incipient productive sector. Objective. To compare the physicochemical and sensory characteristics of whole, skimmed and lactose-free cow and goat milks, as well as their combinations. Materials and methods. In San Jose, Costa Rica, between January and December of 2015, the contents of fat (F), non-fatty solids (NFS), acidity, protein, density, pH, viscosity, and color of the types of milk mentioned were evaluated. Also, a generic descriptive sensory analysis and a general liking test were carried out. Results. Whole goat milk presented higher values of NFS, density and acidity, and lower pH, being whiter than bovine milk, with a similar viscosity. The removal of lactose did not affect viscosity; this factor interacted with the type of milk, but did not affect the fat and protein contents. There was an interaction between the type of milk and the modifications made for the color parameters. The panelists detected significant differences for all the attributes in the products except for the acid aroma. The presence of three clusters was established for the liking test, composed by 37.4 %, 28.8 %, and 34.5 % of the judges. The first and second showed a preference for whole and whole lactose-free cow’s milk and the third for whole and whole-lactose-free cow’s and goat’s milk. The lowest overall liking was for both skimmed and lactose-free bovine and goat samples. Conclusions. The skimming and lactose removal process modified the milk at the physicochemical level, the goat milks with the highest liking were whole and whole lactose-free; the lowest overall liking was for those skimmed-lactose-free in both species.